2021
DOI: 10.3390/jcm10245763
|View full text |Cite
|
Sign up to set email alerts
|

Developing Pulmonary Rehabilitation for COVID-19: Are We Linked with the Present Literature? A Lexical and Geographical Evaluation Study Based on the Graph Theory

Abstract: The Coronavirus Disease 2019 (COVID-19) pandemic is a severe ongoing global emergency. Despite high rates of asymptomatic patients, in many cases, the infection causes a rapid decline in pulmonary function due to an acute respiratory distress-like syndrome, leading to multi-organ failure and death. To date, recommendations about rehabilitation on COVID-19 are based on clinical data derived from other similar lung diseases. Rehabilitation literature lacks a standard taxonomy, limiting a proper evaluation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This might be associated with changes in the small airway that are equivalent to approximately 80% of the extension of the lung parenchyma (35). Given that FEF 25-75% is the only spirometric measurement that assesses the small-caliber airway, additional studies that include more specific diagnostic methods for assessing changes in lung function in the small-caliber airway are needed (36)(37)(38). The long-term impacts of the sequelae of Covid-19 also merit further investigation; the use of a large sample of patients is needed to improve the ability to detect changes in respiratory function before and after therapy.…”
Section: Discussionmentioning
confidence: 99%
“…This might be associated with changes in the small airway that are equivalent to approximately 80% of the extension of the lung parenchyma (35). Given that FEF 25-75% is the only spirometric measurement that assesses the small-caliber airway, additional studies that include more specific diagnostic methods for assessing changes in lung function in the small-caliber airway are needed (36)(37)(38). The long-term impacts of the sequelae of Covid-19 also merit further investigation; the use of a large sample of patients is needed to improve the ability to detect changes in respiratory function before and after therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Of course, specifically designed programs for COVID-19 patients were not available and, pending guidelines dedicated to this new clinical condition, most of the authors have borrowed or adapted pulmonary rehabilitation programs designed for other pathologies [12]. An interesting lexical analysis of the literature showed that rehabilitation in patients with COVID-19 has been focused more on exercises and physical training for the recovery of multiorgan disability and motor impairments, rather than on lung disease [13]. Thus, while providing a comprehensive literature overview, the authors highlighted a discrepancy between the rehabilitation programs proposed for COVID-19 patients and those usually delivered to patients with interstitial lung disease of different etiology.…”
mentioning
confidence: 99%